Serological Survey of Leptospirosis in Thai Swamp Buffalo (Bubalus bubalis) in Sakon Nakhon Province, Thailand - Wongpanit, Kannika; Suwanacharoen, Duangjai; Srikram, Amporn (Agriculture and Natural Resources, 2012)
The study aimed to investigate the seroprevalence of Leptospira infection in swamp buffalo in Sakon Nakhon province, Thailand. Blood samples were collected from 206 swamp buffalo. The microscopic agglutination test was used to test serum samples for speciﬁ c antibodies against 24 serovars of Leptospira antigen (Bratislava, Autumnalis, Ballum, Bataviae, Canicola, Celledoni, Cynopteri, Djasiman, Grippotyphosa, Hebdomadis, Icterohaemorrhagiae, Javanica, Louisiana, Manhao, Mini, Panama, Pomona, Pyrogenese, Ranarum, Sarmin, Sejroe, Shermani, Tarassovi and Patoc). The percentages of buffalo seropositivity against one or more Leptospira serovars were studied. Overall, the prevalence rate was 63.6% (131 out of 206). The prevalent serovars were Shermani, Tarassovi, Pomona, Sejroe, Ranarum, Bratislava, Bataviae, Hebdomadis and Mini. Shermani was the most prevalent serovar (63, 30.6%) followed by Tarassovi (24, 11.7%). Positive samples were found with titers between 1:50 and 1:800, with the highest titers being in the serovar Sejroe.